An occasional record of the amplexus in epigean Niphargus (Amphipoda: Niphargidae) from the Russian Western Caucasus - Marin, Ivan; Palatov, Dmitry (Zootaxa, 2019)
The precopulatory mate guarding (amplexus) was observed in epigean Niphargus cf. magnus Birštein, 1940 collected near Tuapse in the Western Caucasus of Russia. The records of amplexing representatives of the subterranean genus Niphargus Schiödte, 1849 (Crustacea: Amphipoda: Niphargidae) are extremely rare, and there are no publications describing the amplexus in this amphipod genus. The presented report shows that Niphargus have a chemically stimulated short-time amplexus immediately after the molt of the female, similar to the representatives of relative epigean and subterranean gammaridean amphipods. It is relatively short in time, possibly, because of adaptation to inhabit narrows spaces in underground habitats.